Multiple Anesthetic Exposure in Infant Monkeys Alters Emotional Reactivity to an Acute Stressor. (November 2015) - Raper, Jessica; Alvarado, Maria C.; Murphy, Kathy L.; Baxter, Mark G.
Abstract : Background: Retrospective studies in humans have shown a higher prevalence of learning disabilities in children that received multiple exposures to general anesthesia before the age of 4 yr. Animal studies, primarily in rodents, have found that postnatal anesthetic exposure causes neurotoxicity and neurocognitive deficits in adulthood. The authors addressed the question of whether repeated postnatal anesthetic exposure was sufficient to cause long-term behavioral changes in a highly translationally relevant rhesus monkey model, allowing study of these variables against a background of protracted nervous system and behavioral development. Methods: Rhesus monkeys of both sexes underwent either three 4-h exposures to sevoflurane anesthesia (anesthesia group n = 10) or brief maternal separations (control group n = 10) on postnatal day 6 to 10 that were repeated 14 and 28 days later. Monkeys remained with their mothers in large social groups at all times except for overnight observation after each anesthetic/control procedure. At 6 months of age, each monkey was tested on the human intruder paradigm, a common test for emotional reactivity in nonhuman primates. Results: The frequency of anxiety-related behaviors was significantly higher in monkeys that were exposed to anesthesia as neonates as compared with controls: anesthesia 11.04 ± 1.68, controls 4.79 ± 0.77, mean ± SEM across all stimulus conditions. Conclusion: Increased emotional behavior in monkeys after anesthesia exposure in infancy may reflect long-term adverse effects of anesthesia. Abstract : Rhesus monkey infants subjected to three 4-h exposures to sevoflurane manifested increased anxious behavior when confronted with an intruder. The increased anxiety was not attributable to changes in physiologic function during anesthesia. Vocalizations, fear, and irritability behavior, in an age-specific manner, were similar between exposed and nonexposed monkeys. Within a spectrum of behavioral changes induced by neonatal anesthetic exposure, attention should be focused on altered emotional behavior.Supplemental Digital Content is available in the text.